Enhancing Compassion, Communication, And Collaboration Through the Intercultural Ukhuwah-Based English Instructional Model: Evidence from Indonesian Senior High Schools” - Ali, Putri R; Nurwati, Andi; Akhmad, Zulkifli (ELITE JOURNAL, 2025)
ABSTRACT This study addresses a crucial issue in 21st-century education the need to integrate Compassion, Communication, Teamwork, Empathy, and social sensitivity (CCTES) into English language learning to cultivate intercultural competence and social-emotional awareness. The research aims to examine: (1) how the Intercultural Ukhuwah-Based English Instruction (IU-ELT) model fosters students’ compassion, (2) to what extent IU-ELT affects students’ communication skills in intercultural interactions, and (3) how this model enhances students’ ability to work collaboratively. Using a quantitative pre-experimental one-group pretest-posttest design, data were collected from 23 vocational high school students through questionnaires and performance tests, analyzed using descriptive statistics, t-tests, and effect size (Cohen’s d). The findings reveal significant improvement across all variables with large effect sizes, showing IU-ELT effectively strengthens empathy, intercultural communication, and teamwork through values of ta’aruf, tafahum, ta’awun, and takaful. The study concludes that IU-ELT contributes theoretically by bridging intercultural pedagogy with spiritual-based social learning and practically by fostering character, empathy, and collaboration in English classrooms.